Assessment of Larval Health and Metamorphosis of the Giant Freshwater Prawn Macrobrachium rosenbergii Larvae during Acute Exposure to Imidacloprid - Rose, Stephy K. V.; Sruthy, C. Sunil; Chatterjee, Niladri Sekhar; Rangasamy, Anandan (International Journal of Bio-resource and Stress Management, 2023)
An acute toxicity study of imidacloprid on the larval health and metamorphosis of the giant freshwater prawn Macrobrachium rosenbergii larvae were carried out during the months of January–August 2021 at the aquatic animal raring and experimenting facility in the Cochin University of Science and Technology, Kerala, India. Imidacloprid is a broad-spectrum neonicotinoid insecticide used against sucking pests infecting agricultural crops as both contact poison and stomach poison. The present study investigated the adverse effects of imidacloprid on the survival rate, feeding behaviour, larval quality and incidence of metamorphosis in Macrobrachium rosenbergii larvae. The 48 h median lethal concentrations (LC50 values) and safe concentration of imidacloprid determined for different larval stages (Zoea I–XI) of M. rosenbergii ranged between 0.000635–0.001388 mg l-1 and 0.000055–0.000191 mg l-1, respectively. Larvae exposed to imidacloprid for 48 h showed decrease in survival rate with increase in concentration of imidacloprid. The results of larval condition index (LCI) that indicates the larval quality showed that imidacloprid reduced the larval health significantly (p<0.05) at high concentrations and is potent to delay the incidence of metamorphosis. The feeding rate of larvae exposed to different concentrations of imidacloprid were found to be significantly (p<0.05) reduced due to paralytic effect of imidacloprid. The present work provides relevant data beneficial for the risk assessment of imidacloprid in M. rosenbergii.